MiR‐31 and miR‐128 regulates poliovirus receptor‐related 4 mediated measles virus infectivity in tumors - Geekiyanage, Hirosha (Mol Oncol, 2016)
Oncolytic measles virus strains are currently being evaluated in several clinical trials, as a promising novel oncolytic platform. Poliovirus receptor‐related 4 (PVRL4) was recently identified as a potent measles virus (MV) receptor; however, its regulation is not yet understood. Increased levels of PVRL4 protein were observed in cell membrane, cytoplasm and nuclei of glioblastoma, breast and ovarian tumor clinical samples with no significant change in PVRL4 mRNA levels in glioblastoma and breast cancer compared with their corresponding control samples, suggesting that PVRL4 is likely post‐transcriptionally regulated. Therefore, we sought to investigate the potential role of miRNAs in PVRL4 regulation and thus MV infectivity. We demonstrated that miR‐31 and miR‐128 can bind to the 3′UTR of PVRL4 and decrease PVRL4 levels while anti‐miR‐31/128 increase PVRL4 levels suggesting that PVRL4 is miRNA targeted. Furthermore, miR‐31/128 expression levels were down‐regulated in glioblastoma and breast tumor samples and showed significant negative correlations with PVRL4 levels. Infection with an MV strain that exclusively utilizes PVRL4 as its receptor showed that over‐expression of miR‐31/128 decreases MV infectivity while inhibition of the respective miRNAs via anti‐miRs increase MV infectivity and reduce tumor size in mouse xenograft models of glioblastoma, breast and ovarian cancer. Additionally, miR‐128 levels showed significant correlations with MV infection and in vivo anti‐tumor effect, while MV infection increased miR‐31 expression and thereby contributed to the observed decrease in PVRL4 levels. This study suggests that PVRL4 is post‐transcriptionally regulated by miR‐128 and miR‐31 and harbors possible miRNA targets that could modulate MV infectivity and in turn enhance MV based oncolytic therapeutic strategies.